Esketamine induces embryonic and cardiac malformation through regulating the nkx2.5 and gata4 in zebrafish - Shuang Li; Xiang Li; Rui Zhao; Tingyu Jiang; Qiuyun Ou; Huansen Huang; Jiancheng Tang (Scientific Reports, 2025)
Abstract Esketamine (EK) has been widely used in the treatment of depression, but the effects of EK prenatal treatment on embryonic heart development have been rarely reported. This study assesses the effects of varying concentrations of EK on embryonic development and cardiogenesis to determine the teratogenic concentration in the zebrafish model, centering on the interaction between the genes nkx2.5 and gata4 to elucidate the mechanisms underlying cardiac morphogenesis. Zebrafish embryos were classified into six distinct groups and exposed to either a vehicle or EK to ascertain the median lethal concentration (LC50) at 48 and 72 h post-fertilization (hpf) analyzing mortality rate data. Embryonic and cardiac morphologies were assessed utilizing live embryo imaging techniques and stereo microscopy. Nkx2.5 and gata4 were identified via whole-mount in situ hybridization (WISH) and reverse transcription quantitative polymerase chain reaction (RT-qPCR). Exposure to EK leads to significant teratogenic effects on zebrafish embryos, which are both concentration- and time-dependent. The 48 h- and 72 h-LC50 of EK for zebrafish embryos were 1.30 (95% CI 0.92, 1.60) millimolar (mM) and 0.71 (95% CI 0.46, 1.01) mM, respectively. A significant reduction in heart rates and body length were observed and the distance between the sinus venosus and bulbar artery (SV-BA) was found expanded, the pericardial edema area showed significant swelling, and the body axis curvature was more pronounced in the EK exposure groups. Both WISH an RT-qPCR analysis showed nkx2.5 staining intensity and expression significantly decreased, while gata4 assay results were in the opposite direction. Our findings indicate that exposure of zebrafish embryos to EK results in embryonic and cardiac malformations, primarily due to the down-regulation of nkx2.5 and the over-expression of gata4. Equilibrium maintenance and compensatory mechanisms are crucial in spatiotemporal gene regulation.